Kajian Kimia Medisinal Ciprofloxacin: Mekanisme Kerja, Antibakteri, dan Pola Resistensi Bakteri - Saeful Amin; Fuza Khoirun Nisa; Yosi Setiawati; Muhammad Akbar Alfi Fauzan (Lembaga Pengembangan Kinerja Dosen, 2025)
Ciprofloxacin is a fluoroquinolone antibiotic that is widely used in the treatment of various bacterial infections. This study aims to analyze the mechanism of action of ciprofloxacin from a medicinal chemistry perspective, evaluate its antibacterial effectiveness against pathogenic bacteria, and identify the developing resistance patterns. The method used is a literature study by reviewing various relevant scientific literature. The results of the study indicate that ciprofloxacin works by inhibiting the enzymes DNA gyrase and topoisomerase IV, which play an important role in bacterial DNA replication and transcription, causing DNA fragmentation and bacterial cell death. Ciprofloxacin shows high antibacterial activity against Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Vibrio cholerae. However, resistance to ciprofloxacin continues to increase, mainly due to target gene mutations, increased expression of efflux pumps, and changes in porin structure. A deep understanding of the structure-activity of ciprofloxacin is important in the development of new derivatives that are more effective and able to overcome resistance. This study provides important insights into the innovation of more robust antimicrobial drug design.